(untitled) (Research, Society and Development, 2021)
A variety of alternative media were important tools of resistant in a Brazil that was deep in civil and military dictatorship (1964-1985). Several minority groups were considered subversive and accused of trying to oppose morals and good manners. Among them are those formed by gays, lesbians, transvestites and transsexuals. Some political groups composed of excluded populations were created to withstand against these forms of oppression and to give visibility to its causes, like the GALF – Grupo de Ação Lésbico-Feministas (Group of Action Lesbian-Feminist) and SOMOS group. This period was devastating for issues of individual liberties, especially for the population and the LGBT movement. The creation of alternatives medias like the Lampião da Esquina publications / newspaper (1978-1981) and the bulletin ChanacomChana (1981-1987), was an important step in the battle for the recognition of such population. These alternatives medias presented questions related to daily life, the arts, and politics. This work aims to make and analyze the narrative review of literature on the two journals, for that purpose we conducted the search in the databases Scielo, BDTD, and Periódicos Capes. The descriptors were: Lampião da Esquina, Chana with Chana and Chanacomchana. Where returned 20 theses and dissertations and 20 articles based on these descriptors. After quantifying and categorizing the results, it is observed that there were few studies on the ChanacomChana bulletin, a thesis and an article. Such works analyze the journals as processes of resistance, trans / gay and lesbian visibility / invisibility, identities, body, and literature.